Effects of Denture Base Thicknesses and Reinforcement on Fracture Strength in Mandibular Implant Overdenture with Bar Attachment: Under Various Acrylic Resin Types - Tokgoz, Selen; Ozdiler, Arda; Gencel, Burc; Bozdag, Ergun; Isık-Ozkol, Gulbahar (European Journal of Dentistry, 2019)
Objective This study aimed to assess the effect of reinforcement, denture base thickness, and acrylic resin types on dynamic and static fracture strength in mandibular implant overdentures with bar attachment.Materials and Methods One hundred and eight experimental mandibular implant overdentures with bar attachments were fabricated in three main groups, namely unreinforced (control: C), reinforced with unidirectional glass fibers (FR), and Co–Cr cast metal (MR). Each group included denture bases of 2-, 3-, and 4-mm thicknesses and produced with conventional (CA) and high-impact acrylic (HIA) resins. Specimens were thermocycled (5,000 times, 5–55°C) then subjected to a 400,000 cyclic load regime. Unbroken specimens were then loaded until fracture by a universal testing machine. Differences in mean fracture resistance among the groups were compared using the one-way analysis of variance (with post hoc Tukey's honestly significant difference test) and Student's t-tests (α = 0.05).Results Fracture strength increased significantly when the denture base thickness was increased (p = 0.001). The 2-mm denture base thickness was not enough for reinforcement. The fracture strength of the FR groups was significantly higher than other groups for 3- and 4-mm thicknesses (p = 0.001). The fracture strength of the HIA resin was significantly higher than CA resin in FR groups (p = 0.029 and p = 0.001). MR groups showed the weakest fracture strength.Conclusions The 2-mm denture base thickness had sufficient fracture strength without reinforcement and a positive relationship between acrylic resin thickness and fracture resistance was found.
Keywords: denture base thickness; dynamic loading; overdenture